The Effects of Intelectin-1 on Antioxidant and Angiogenesis in HUVECs Exposed to Oxygen Glucose Deprivation - Gu, Naibing; Wang, Jun; Di, Zhengli; Liu, Zhiqin; Jia, Xiaotao; Yan, Yu'e; Chen, Xiaoshan; Zhang, Quanzeng; Qian, Yihua (Frontiers in Neurology, 2019)
Objective: Ischemic stroke leads to cellular death and tissue damage by depriving the areas of glucose and oxygen supplies. The effective treatment of stroke remains a challenge for modern medicine. This study used an oxygen-glucose deprivation (OGD) model of human umbilical vein endothelial cells (HUVECs) to mimic ischemic injuries and explored the role and mechanism of intelectin-1. Methods: Intelectin-1 was transduced into the HUVECs using a lentiviral vector. To examine the potential involvement of PI3K/Akt signaling in intelectin-induced eNOS phosphorylation, HUVECs were treated with PI3K inhibitor LY294002. Results: Our results demonstrated an increase in capillary density, decrease in apoptotic cells, and increase in HIF-1α protein expression following intelectin-1 treatment. Real-time PCR and Western blotting revealed the increased intelectin-1 expression alongside eNOS and Akt phosphorylation with enhanced bcl-2 expression under OGD. Capillary density decreased significantly after LY294002 treatment. Conclusion: These results suggest intelectin-1 promotes angiogenesis, inhibits oxidative stress and reduces apoptosis by stimulating the Akt-eNOS signaling pathway in response to ischemia in vitro.